Antena Helix Mode Axial untuk Frekuensi Kerja Radar S-Band - M. Reza Hidayat; Aditya Febryana; Nivika Tiffany Somantri; Yussi Perdana Saputera (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2023)
This study designed an axial mode helix antenna with a working frequency used of 2.1 GHz, which has a return loss value of < -10 dB and VSWR < 1.3. The simulation was carried out using the CST studio suite 2020 software by designing a helix antenna from the calculation results to optimization of the helix antenna structure, namely the distance between the windings, the number of windings, the diameter of the windings, and the diameter of the ground plane until the simulation results are in accordance with the specifications of the desired parameters. Based on the final results of the return loss parameters and VSWR has met the designed specification standards, from the simulation results of the axial mode helix antenna, the results were obtained, namely at a return loss of -22 dB and at a VSWR value obtained 1.17. The results of the measurement of the axial mode helix antenna obtained the same result at a return loss of -22 dB and at VSWR 1.17 but the frequency value used in the measurement shifted to 2.45 GHz, this is not a problem because the s-band frequency can work from 2 GHz to 4 GHz.